EFEK REAKSI PADA SIFAT TRANSPORT GAS RAPAT BINER - I Gusti Made Sanjaya, (Matematika dan Sains, 2011)
Effect of chemical reaction was discribed using the hard ball collision model and the present chemical reaction model on properties of the binary dense gas transport experiencing reversible reaction according to equation : A + A B + B. The reactive collision used near the final condition ofreaction, with the smallest of chemical affinity and near equilibrium. Discussion was done through framework of gas kinetic theory using base of extended of Boltzman equation. Effect of chemical reaction was found to appear in coefficient of gas transport as at bulk viscosity in form e*/kT. e*/kT.